K-Ar age determination, whole-rock and oxygen isotope geochemistry of the post-collisional Bizmisen and Calti plutons, SW Erzincan, eastern Central Anatolia, Turkey - Önal, A; Boztug, D; Kürüm, S; Harlavan, Y; Arehart, GB; Arslan, M (Wiley, 2005)
Post-collisional granitoid plutons intrude obducted Neo-Tethyan ophiolitic rocks in central and eastern Central Anatolia. The Bizmisen and Calti plutons and the ophiolitic rocks that they intrude are overlain by fossiliferous and flyschoidal sedimentary rocks of the early Miocene Kemah Formation. These sedimentary rocks were deposited in basins that developed at the same time as tectonic unroofing of the plutons along E-W and NW-SE trending faults in Oligo-Miocene time. Mineral separates from the Bizmisen and Calti plutons yield K-Ar ages ranging from 42 to 46 Ma, and from 40 to 49 Ma, respectively. Major, trace, and rare-earth element geochemistry as well as mineralogical and textural evidence reveals that the Bizmisen pluton crystallized first, followed at shallower depth by the Calti pluton from a medium-K calcalkaline, I-type hybrid magma which was generated by magma xing of coeval mafic and felsic magmas. Delta O-18 values of both plutons fall in the field of I-type granitoids, although those of the Calti pluton are consistently higher than those of the Bizmisen pluton. This is in agreement with field observations, petrographic and whole-rock geochemical data, which indicate that the Bizmisen pluton represents relatively uncontaminated mantle material, whereas the Calti pluton has a significant crustal component. Structural data indicating the middle Eocene emplacement age and intrusion into already obducted ophiolitic rocks, suggest a post-collisional extensional origin. However, the pure geochemical discrimination diagrams indicate an arc origin which can be inherited either from the source material or from an upper mantle material modified by an early subduction process during the evolution of the Neo-Tethyan ocean. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: K-Ar dating; whole-rock geochemistry; oxygen isotope geochemistry; geodynamics; Bizmisen and Calti plutons; Erzincan; Turkey